2018
DOI: 10.3389/fpsyg.2018.01713
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Effects of Psychopathic Traits on Executive Functioning: Insights From the Triarchic Model

Abstract: The relationship between executive functioning and psychopathy lacks consistent findings. The heterogeneity of the psychopathic personality structure may contribute to the mixed data that emerged from clinical-categorical approaches. Considering the link between antisocial behavior and executive dysfunction from the perspective of the Triarchic Model of Psychopathy, it is suggested that executive impairments in psychopathy are specifically explained by meanness and disinhibition traits, reflecting externalizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…From this standpoint, 3-dimensional models of psychopathy (see Figure 1) claimed more recently for a hierarchical organization of the psychopathic personality structure, in which deficits in personality (i.e., interpersonal-affective features) may be (or not) a risk factor for behavioral outcomes (i.e., impulsive-antisocial; Cooke & Michie, 2001;Cooke et al, 2006;Patrick, 2006;Skeem et al, 2011). Antisocial tendencies are expected to co-vary with psychopathy, but this association is merely probabilistic and not linearly determined, as other individual and contextual risk factors (e.g., deficits in cognitive functioning and the lack of care experiences in infancy) are expected to moderate this association (Cooke & Michie, 2001;Pasion et al, 2018a;Patrick, 2006;. Within the scope of 3-dimensional models, antisocial behavior does not constitute a core feature of psychopathy per se and is best viewed as a possible second-order outcome of primary deficits in the interpersonal and affective dimensions.…”
Section: Contemporary Models: Encompassing Adaptive and Maladaptive Expressions Of Psychopathymentioning
confidence: 99%
See 3 more Smart Citations
“…From this standpoint, 3-dimensional models of psychopathy (see Figure 1) claimed more recently for a hierarchical organization of the psychopathic personality structure, in which deficits in personality (i.e., interpersonal-affective features) may be (or not) a risk factor for behavioral outcomes (i.e., impulsive-antisocial; Cooke & Michie, 2001;Cooke et al, 2006;Patrick, 2006;Skeem et al, 2011). Antisocial tendencies are expected to co-vary with psychopathy, but this association is merely probabilistic and not linearly determined, as other individual and contextual risk factors (e.g., deficits in cognitive functioning and the lack of care experiences in infancy) are expected to moderate this association (Cooke & Michie, 2001;Pasion et al, 2018a;Patrick, 2006;. Within the scope of 3-dimensional models, antisocial behavior does not constitute a core feature of psychopathy per se and is best viewed as a possible second-order outcome of primary deficits in the interpersonal and affective dimensions.…”
Section: Contemporary Models: Encompassing Adaptive and Maladaptive Expressions Of Psychopathymentioning
confidence: 99%
“…A longstanding research question in the field leans on whether antisocial behavior is a coherent part of the psychopathic personality structure. Some theoretical models argue that antisocial behavior is inherently blended in the construct of psychopathy Neumann et al, 2007), while others postulate that this association is not linear and depends on the intersection with other risk factors (Cooke & Michie, 2001;Pasion et al, 2018a;Patrick, 2006;. Therefore, critical processes that may underpin psychopathy and antisocial behaviore.g., empathymay be critical to examine points of convergence/divergence between both constructs.…”
Section: Psychopathy Vs Antisocial Behavior: the Differential Role Of Cognitive And Affective Empathymentioning
confidence: 99%
See 2 more Smart Citations
“…FD was associated with reduced stress and positive adaptive coping styles (Dalkner et al, 2015), professional satisfaction and material success (Eisenbarth et al, 2018;Howe et al, 2014), higher income (Lilienfeld et al, 2014), authentic pride , leadership (Lilienfeld & Windows, 2005), and adaptive behaviours (Young-Lundquist et al, 2012). Moreover, two papers explored the relationship between EF and psychopathic personality traits (Lantrip, Towns, Roth, & Giancola, 2016;Pasion, Cruz, & Barbosa, 2018), which demonstrated that FD was associated with better emotional control and cognitive flexibility. This suggests that affective-interpersonal traits (e.g., superficial charm, lack of empathy, and manipulation; as defined by PPI-R & TriPM), such as FD, can enhance specific aspects of EF.…”
Section: Synthesis Of Major Findingsmentioning
confidence: 99%